Dietary vitamin C supplementation improves semen quality and antioxidant activity in Japanese quail under summer heat stress - Aimen Jahangir; Shamim Akhter; Sumiyyah Zuha; Bushra Allah Rakha; Hajrah Raad Tihami; Hafsah Tihami (Ovozoa: Journal of Animal Reproduction, 2026)
Heat stress severely affects the redox balance of poultry semen, as the limited supply of natural antioxidants is unable to neutralize the excessive production of free radicals. This oxidative stress can reduce sperm quality and reproductive productivity in Japanese quails during summer. Dietary supplementation may provide a cost-effective approach to maintaining semen quality under such conditions. The present study was conducted to assess the effects of dietary vitamin C on semen volume, antioxidant activity, sperm concentration, motility, viability, plasma membrane integrity, and acrosomal and DNA integrity over four weeks. Thirty male Japanese quails were maintained at an ambient temperature of 35-40 °C (May-June), divided into five groups, and supplemented with 40, 80, 150, or 170 mg vitamin C/kg diet, with a control group, for four weeks. Semen was collected weekly by manual massage, and sperm parameters were evaluated using three replicates per group per week. Vitamin C supplementation did not significantly affect semen volume (p> 0.05). However, semen quality parameters and antioxidant activity increased significantly (p< 0.05) up to the third week, with no further increase in the fourth week. The 150 mg/kg treatment showed the highest sperm concentration, motility, viability, plasma membrane integrity, acrosomal integrity, DNA integrity, and antioxidant activity at week three, with these values maintained in the fourth week. Thus, dietary vitamin C at 150 mg/kg may help maintain semen quality and antioxidant activity in Japanese quails during summer heat stress.